I walk, therefore I am: a multidimensional study on the influence of the locomotion method upon presence in virtual reality. Issue 5 (9th April 2020) - Soler-Domínguez, José L; de Juan, Carla; Contero, Manuel; Alcañiz, Mariano
Abstract: A defining virtual reality (VR) metric is the sense of presence, a complex, multidimensional psychophysical construct that represents how intense is the sensation of actually being there, inside the virtual environment (VE), forgetting how technology mediates the experience. Our paper explores how locomotion influences presence, studying two different ways of artificial movement along the VE: walking-in-place (through head bobbing detection) and indirect walking (through touchpad). To evaluate that influence, a narrative-neutral maze was created, from where 41 participants ( N =41) had to escape. Measuring presence is a controversial topic since there is not a single, objective measure but a wide range of metrics depending on the different theoretical basis. For this reason, we have used for the first time, representative metrics from all three traditional dimensions of presence: subjective presence (SP) (self-reported through questionnaires), behavioral presence (BP) (obtained from unconscious reactions while inside the VE), and physiological presence (PP) [usually measured using heart rate or electrodermal activity (EDA)]. SP was measured with the ITC-SOPI questionnaire, BP by collecting the participants' reactions, and PP by using a bracelet that registered EDA. The results show two main findings: (i) There is no correlation between the different presence metrics. This opens the door to a simpler way of measuring presence in an objective, reliable way. (ii) There is no significant difference between the two locomotion techniques for any of the three metrics, which shows that the authenticity of VR does not rely on how you move within the VE. Graphical Abstract: